The Influence of Institutional Resources on Doctorate Degree Enrolment and Completion Rates in Selected Public Universities Kenya - Jared Ochwangi , Motanya; Salome, Nyambura; Mugo, Gathara Peter (International Journal of Learning and Development, 2024)
Doctorates are fundamental pivot towards facilitating the social and economic transformation of a nation. Nevertheless, research on doctorate education point out that most candidates in Kenyan public universities spend lengthy period of time to earn their doctorate degrees. Furthermore, data of those enrolling in selected Kenyan public universities demonstrate that less students enroll for doctorate programmes in contrast with those who register for Master and Bachelors’ programmes. Institutional resources have been cited as a critical ingredient toward enhanced students’ enrolment into doctorate programmes. The purpose of this paper was, therefore, to establish the influence of institutional resources on doctorate degree enrolment and completion rates from selected Kenyan public universities. The study sought to analyse institutional resources influence on doctorate degree programmes enrolment and completion rates from selected public universities in Kenya for the last fifteen years. The study employed the mixed methods research design. Data was collected from four purposively sampled universities using questionnaires, analysis of documents (on enrolment, completion and staff enrolments) and interview schedules. Qualitative data was coded and then thematically analysed guided by the study objectives while quantitative data was analysed using percentages and graphs. The study revealed that institutional resources influence enrolment and completion rates at doctorate level. Availability of qualified and sufficient academic staff, funding, mentorship programmes, well equipped libraries, reliable internet connections and ambient social environment to be critical in determining where one enrolls for a doctorate programme and how long it will take to complete. The study furthermore established that between 2003 and 2017, there was low doctorate programmes enrolment and completion rates at the selected public Universities Kenya. This was demonstrated from trends in the numbers of those who enrolled and those who graduated. The trends revealed that more males than females enrolled and completed their studies with the highest being between 2008 and 2013. The findings of this research would be resourceful to university policy makers, administrators and lecturers to improve on institutional policy framework with regard to institutional resources which could be used to enhance doctorate programme enrolment and completion in Kenyan public universities.